A new widely distributed invasive alien species of Amasa ambrosia beetles (Coleoptera: Curculionidae: Scolytinae: Xyleborini) - Knížek, Miloš; Smith, Sarah M. (Zootaxa, 2024)
Amasa parviseta Knížek & Smith, new species is described from Australia, Brazil, Uruguay, France and Spain. The species is native to Australia and appears to have spread widely in association with introduced Eucalyptus species.